Konsep Pendidikan Holistik di Sekolah Dasar Islam Terpadu (SDIT) Assajidin Sukabumi - Siti Ulfah Fauziah; Siti Qomariyah; Rubi Babullah; Najrul Jimatul Rizki; Ujang Natadireja (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This study aims to gain an in-depth understanding of the holistic education concept applied in the Assajidin Integrated Islamic Elementary School (SDIT). The study used a qualitative approach involving the participation of 7 teachers and 20 students as key informants. Data was collected through in-depth interviews, class observations, and analysis of related documents. The results of the study show that SDIT Assajidin applies a holistic educational approach that includes intellectual, emotional, physical, social and spiritual aspects. Teachers at SDIT Assajidin act as facilitators in creating a learning environment that supports the overall development of students. They use a variety of active, innovative, and creative learning strategies to facilitate students' conceptual understanding and character development. In addition, students at SDIT Assajidin are actively involved in learning through group discussions, collaborative projects, and relevant extracurricular activities. This learning process helps students to develop critical thinking skills, creativity, communication, cooperation, and leadership. During the implementation of the curriculum, SDIT Assajidin instilled Islamic values ​​in all aspects of learning, both in religious and non-religious subjects. Teachers also help students understand and apply Islamic values ​​in everyday life through examples and real experiences. This study provides an overview of the implementation of the holistic education concept at SDIT Assajidin. The results of this study are expected to provide deeper insight and understanding of holistic educational practices in an integrated Islamic school environment. The implications of this research can be used as input for curriculum development and holistic educational practices at SDIT as well as being a reference for other schools interested in adopting a similar approach.